2022
DOI: 10.1111/ddi.13547
|View full text |Cite
|
Sign up to set email alerts
|

Large mountains make small barriers: Species composition and spatial dynamics history of the Odorrana schmackeri complex in the karst area of Guizhou, China

Abstract: Aim Species delimitation is the basis for identifying diversity, and the genetic structure and demographic history of species can shed light on the effects of geological and historical climate change, thus allowing us to develop appropriate conservation and management strategies. In this study, we aimed to clarify the species composition and geographic distribution of the Odorrana schmackeri complex in the karst areas of Guizhou, explore the influence of geological and climatic events on its evolutionary and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…Jiang, Yan et al (2022) mapped the spatial distributions of 1028 endemic true bugs in China and investigated the distribution and diversity of endemic true bugs for four family groups (i.e., Miridae, Lygaeoidea, Pentatomidae, and Reduviidae), the environmental factors shaping these diversity patterns, and the effectiveness of China's Protected areas (PAs) in safeguarding their diversity. They found that most (84.9%) diversity hotspots for total species were located in mountainous areas of southern China.…”
Section: This Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Jiang, Yan et al (2022) mapped the spatial distributions of 1028 endemic true bugs in China and investigated the distribution and diversity of endemic true bugs for four family groups (i.e., Miridae, Lygaeoidea, Pentatomidae, and Reduviidae), the environmental factors shaping these diversity patterns, and the effectiveness of China's Protected areas (PAs) in safeguarding their diversity. They found that most (84.9%) diversity hotspots for total species were located in mountainous areas of southern China.…”
Section: This Issuementioning
confidence: 99%
“…fissipes populations. Jiang, Dong et al (2022) found Miaoling Mountains were not a geographical barrier to the dispersal of Schmacker's frog, Odorrana kweichowensis and O . huanggangensis , and the Dalou Mountains, Foding‐Wuling‐Leigong‐Yueliang Mountains were geographical distribution boundaries in the formation of the current distribution of the three species in Guizhou Province.…”
Section: This Issuementioning
confidence: 99%
“…Past climatic changes, particularly during the late Pleistocene, have been important drivers of variations in genetic structure, demographic fluctuations and the current distributions of many extant species (Hewitt, 2000(Hewitt, , 2004Ye et al, 2014Ye et al, , 2022Zhang et al, 2022). Geological events such as the formation of mountain systems can generate physical barriers to dispersal, resulting in population differentiation and speciation (Che et al, 2010;Jiang et al, 2022;Zhu et al, 2022). Contemporary factors, including human-mediated factors, can also strongly affect geographic distributions and genetic variations within a population (Cao et al, 2017(Cao et al, , 2021Drahun et al, 2021;Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary factors, including human-mediated factors, can also strongly affect geographic distributions and genetic variations within a population (Cao et al, 2017(Cao et al, , 2021Drahun et al, 2021;Xu et al, 2022). Determining how past and present factors have contributed to population genetic patterns enables a deeper understanding of the evolutionary history and ecological adaptations of a species, which contributes to the development of appropriate conservation and management strategies (Drahun et al, 2021;Jiang et al, 2022;Sherpa et al, 2022;Wang et al, 2021;Ye et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation